Peripheral loss of regulatory T cells and polyautoimmunity in an HIV-infected patient. (November 2018) - Quiros-Roldan, E; Zanini, B; Ferraresi, A; Castellano, M; Giustini, V; Sottini, A; Castelli, F; Imberti, L
We report a case of a human immunodeficiency virus (HIV)/hepatitis C virus-co-infected patient with an optimal virological status but with a poor CD4+ cell profile, followed up in the University Department of Infectious and Tropical Diseases of Brescia, Italy. He presented several autoimmune diseases (ADs) over the years concomitant with CD4+ cell increase episodes following severe immune depression of unknown cause. We studied T- and B-cell subsets and found low levels of K-deleting Recombination Excision Circles, T-cell Receptor Excision Circles and B and T memory subpopulations, which indicated that the bone marrow and thymic outputs were lower than in healthy controls. The most relevant phenotypic alteration was in the regulatory T-cell (Treg) population, because total Tregs as well as naïve, central memory and effector memory cells were detected at very low levels. This was the first case of polyautoimmunity defined as the presence of more than one AD in the same individual, occurring in an HIV patient. Several factors may be implicated, including genetic susceptibility, environmental factors, concomitant therapies and dysregulation of immune system cells. The extremely low number of Tregs found in our patient may play a major role in the regulation of the immune response and the development of all ADs.